Spatiotemporal variations of chlorinated paraffins in PM2.5 from Chinese cities: Implication of the shifting and upgrading of its industries. (April 2020) - Liu, Di; Li, Qilu; Cheng, Zhineng; Li, Kechang; Li, Jun; Zhang, Gan
Abstract: To highlight the levels and distributions and to assess the risk of human exposure of chlorinated paraffins (CPs) in PM2.5 in China, the concentrations and homologue patterns of short−chain chlorinated paraffins (SCCPs) and medium−chain chlorinated paraffins (MCCPs) in PM2.5 from 10 cities in China were studied in 2013 and 2014. The mean concentrations of ΣSCCPs and ΣMCCPs were 19.9 ± 41.1 ng m −3 and 15.6 ± 18.6 ng m −3, respectively. Unexpectedly, the highest pollution levels occurred in two central cities (Xinxiang and Taiyuan) rather than in well−known eastern megacities such as Beijing, Nanjing, Shanghai, and Guangzhou. By comparing with earlier research, it has indicated the trend of CPs industry shifting from large eastern cities to small and medium-sized cities in central China to some extent. In addition, the composition pattern of SCCPs demonstrated an obviously differences from previous studies, with C11 and Cl7 predominating and accounting for 45.1% and 24.9%, respectively. Meanwhile, the ratio of MCCPs/SCCPs in most cities was less than 1.00 except for Guangzhou (1.92), Shanghai (1.29), and Taiyuan (1.11). Combined with the results of correlation analysis and principal component analysis, the observed pollution characteristics of CPs in PM2.5 had similar sources, which were more influenced by the ratio of MCCPs/SCCPs than by organic carbon, elemental carbon, temperature, population, and gross domestic product. Overall, the composition of CPs reflected the characteristics of local industrial production and consumption, and also implied efforts of Chinese enterprises to reduce the content of short carbon groups of CPs production. The CPs mainly deposited in head airways during the process of entering the human respiratory system. However, at the present levels, there was no significant carcinogenic effect for human health. Graphical abstract: Image 1 Highlights: The highest levels occurred in two relatively less developed central cities. C11 and Cl7 homologues were dominant in this work. The ratio of MCCPs/SCCPs in most cities was less than 1.00. Local industrial production and consumption determined the chlorinated paraffins (CP) characteristics.